The Politics of Water Institutional Reform in Neopatrimonial States A Comparative Analysis of Kyrgyzstan and Tajikistan - Sehring, Jenniver; SpringerLink (Online service) (Wiesbaden : VS Verlag für Sozialwissenschaften, 2009)
In many countries, water institutional reforms (like the establishment of water user associations or the introduction of pricing mechanisms) are conducted in order to achieve more sustainable, efficient, and equitable water usage. Often, however, these reforms do not meet their objectives. Based on a comparative analysis of Kyrgyzstan and Tajikistan, this study highlights the long neglected role of politics. It shows how a neopatrimonial regime context impacts the reform process, focusing on the decision making, the agricultural sector, the local governance institutions, internal water-institutional linkages, and the role of international donor agencies.
Water Governance and Water Institutional Reform -- Theoretical Framework: New Institutionalism -- Analytical framework -- Comparative Research Design -- Water Institutional Reforms in Kyrgyzstan -- Water Institutional Reforms in Tajikistan -- Comparing the Politics of Water Institutional Reform -- Conclusion.
Keywords: Political science; Comparative politics; Political Science and International Relations; Political Science; Comparative Politics; Electronic books